2018
DOI: 10.3390/su10114259
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Travelers’ Behavior for Sustainable Smart Tourism: A Technology Readiness Perspective

Abstract: Smart tourism has contributed to making people’s travels easier and more enjoyable, but sometimes has a negative impact on their travel experience. The challenges travelers face while using smart devices have not been researched in detail and are relatively unknown. While most studies have considered the usefulness of smart devices in tourism, negative perceptions of smart tourism have rarely been discussed. Thus, this study investigates travelers’ risk perceptions of smart tourism from a technology readiness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 72 publications
0
20
0
6
Order By: Relevance
“…Perceived risk is a strong antecedent to consumers' behavioral beliefs, attitude, and intention in various information systems contexts [11,51,55]. Prior research found that the higher the perception of risk, the more negative is its influence on beliefs, attitude, intention, and actual behavior.…”
Section: Antecedents Of Negative Attitude: Psychology Risk Social Rimentioning
confidence: 99%
“…Perceived risk is a strong antecedent to consumers' behavioral beliefs, attitude, and intention in various information systems contexts [11,51,55]. Prior research found that the higher the perception of risk, the more negative is its influence on beliefs, attitude, intention, and actual behavior.…”
Section: Antecedents Of Negative Attitude: Psychology Risk Social Rimentioning
confidence: 99%
“…2018), Penelitian ini membahas pariwisata cerdas telah berkontribusi untuk membuat perjalanan orang lebih mudah dan lebih menyenangkan, tetapi terkadang memiliki dampak negatif pada pengalaman perjalanan mereka (dampak optimisme, inovasi, rasa tidak aman, dan ketidaknyamanan). [3] Penelitian ini menyelidiki persepsi risiko wisatawan tentang pariwisata cerdas dari perspektif kesiapan teknologi. Hasil penelitian menunjukkan bahwa manfaat yang dirasakan dari perangkat pintar memiliki pengaruh signifikan terhadap niat penggunaan perangkat cerdas ketika dalam perjalanan.…”
Section: Kajian Penelitian Terkaitunclassified
“…"Understanding Travelers' Behavior for Sustainable Smart Tourism: A Technology Readiness Perspective" by Pradhan et al (Paper Number 6) [20] shows how smart tourism has contributed to making people's travels easier and more enjoyable, even if sometimes it has a negative impact on their travel experience. In fact, while most studies have considered the usefulness of smart devices in tourism, negative perceptions of smart tourism have rarely been discussed.…”
Section: Form and Contents Of The Thematic Issuementioning
confidence: 99%